Representation of Women's Struggle against Violence and Gender Discrimination in the Film “Women from Rote Island” - Wulandari, Wulandari; Christine, Anastasya; Reftantia, Ghina; Sartika, Diana Dewi; Saraswati, Erlisa (Saree: Research in Gender Studies, 2025)
ABSTRACT ENGLISH: Film is a mass communication media that combines audio and visual elements to convey messages to a wide audience. As a cultural product, film uniquely represents social realities, shapes public opinion, and serves as a platform for reflecting on various human issues. In the modern era, film has evolved into an effective tool for voicing social criticism and highlighting marginalized issues in public discourse, including violence and gender discrimination. One such film is Women from Rote Island, which focuses on the experiences of women in Eastern Indonesia who face domestic violence and structural discrimination. The film portrays how women fight to uphold their rights and dignity amid strong patriarchal cultural pressures. Through emotional storytelling and symbolic visuals, the film delivers messages of resistance against the injustices experienced by women. This article aims to analyse the representation of women's struggles in Women from Rote Island using Roland Barthes' semiotic theory. This theory is applied to explore the denotative (literal) and connotative (symbolic or cultural) meanings of the signs presented in the film—ranging from imagery, character expressions, and dialogue to setting. The research employs a qualitative method with a descriptive approach, allowing the researcher to interpret the hidden messages and meaning structures constructed by the film. The analysis reveals that this film not only represents the social realities faced by women but also serves as a symbolic resistance to an unjust social system. It succeeds in building audience empathy and encouraging critical awareness of issues related to gender-based violence and discrimination. Thus, film can be seen as an effective alternative medium in voicing women's struggles and advocating for gender equality. ABSTRACT INDONESIAN: Film merupakan salah satu bentuk media komunikasi massa yang menggabungkan elemen audio dan visual untuk menyampaikan pesan. Sebagai produk budaya, film memiliki kemampuan unik dalam merepresentasikan realitas sosial, membentuk opini publik, serta menjadi wadah refleksi terhadap berbagai isu kemanusiaan. Di era modern, film berkembang menjadi alat yang efektif dalam menyuarakan kritik sosial dan mengangkat persoalan-persoalan yang sering kali terpinggirkan dalam wacana publik, termasuk isu kekerasan dan diskriminasi gender. Salah satu film yang mengangkat isu tersebut adalah Women from Rote Island, sebuah film yang berfokus pada pengalaman perempuan di wilayah Timur Indonesia yang menghadapi kekerasan dalam rumah tangga dan diskriminasi struktural. Film ini menggambarkan bagaimana perempuan berjuang mempertahankan hak dan martabatnya di tengah tekanan budaya patriarkis yang kuat. Melalui narasi yang emosional dan visual yang simbolis, film ini menyampaikan pesan-pesan perlawanan terhadap ketidakadilan yang dialami perempuan. Artikel ini bertujuan untuk menganalisis representasi perjuangan perempuan dalam film Women from Rote Island dengan menggunakan teori semiotik Barthes. Teori ini digunakan untuk menggali makna denotatif (makna literal) dan konotatif (makna simbolik atau kultural) dari tanda-tanda yang muncul dalam film, baik berupa gambar, ekspresi tokoh, dialog, maupun latar tempat. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, yang memungkinkan peneliti untuk menginterpretasikan pesan-pesan tersembunyi dan struktur makna yang dibangun oleh film. Hasil penelitian ini menunjukkan bahwa film ini tidak hanya merepresentasikan kenyataan sosial yang dihadapi perempuan, tetapi juga menjadi sarana perlawanan simbolik terhadap sistem sosial yang tidak adil. Film ini berhasil membangun empati penonton dan mendorong kesadaran kritis terhadap isu kekerasan dan diskriminasi gender. Dengan demikian, film dapat dilihat sebagai media alternatif yang efektif dalam menyuarakan perjuangan perempuan serta memperjuangkan kesetaraan gender.